Role of isotope mass and evidence of fluctuating zonal flows during the L–H transition in the TJ-II stellarator. (10th May 2018) - Losada, U; Estrada, T; Liu, B; van Milligen, B; Cheng, J; Silva, C; Pastor, I; Fontdecaba, J M; Hidalgo, C
Abstract: Mean radial electric fields as well as low frequency Zonal Flow-like global oscillations in radial electric field have been identified during the low to high (L–H) transition in Hydrogen and Deuterium dominated plasmas in the stellarator TJ-II. No evidence of isotope effect on the L–H transition dynamics was observed in the investigated TJ-II plasma scenarios. These observations emphasize the critical role of both zero frequency (equilibrium) and low frequency varying large-scale flows for stabilizing turbulence during the triggering of the L–H transition in magnetically confined toroidal plasmas.